Ag-Contained Superabsorbent Curdlan-Chitosan Foams for Healing Wounds in a Type-2 Diabetic Mice Model - Elizaveta S. Permyakova; Anton S. Konopatsky; Konstantin I. Ershov; Ksenia I. Bakhareva; Natalya A. Sitnikova; Dmitry V. Shtansky; Anastasiya O. Solovieva; Anton M. Manakhov (MDPI AG, 2022)
This study focused on the synthesis and characterization of pure curdlan-chitosan foams (CUR/CS), as well as foams containing Ag nanoparticles (CUR/CS/Ag), and their effect on the skin repair of diabetic mice (II type). The layer of antibacterial superabsorbent foam provides good oxygenation, prevents bacterial infection, and absorbs exudate, forming a soft gel (moist environment). These foams were prepared from a mixture of hydrolyzed curdlan and chitosan by lyophilization. To enhance the antibacterial properties, an AgNO3 solution was added to the curdlan/chitosan mixture during the polymerization and was then reduced by UV irradiation. The membranes were further investigated for their structure and composition using optical microscopy, scanning electron microscopy, energy-dispersive spectroscopy, FT-IR spectroscopy, and XPS analysis and modeling. In vivo tests demonstrated that CUR/CS/Ag significantly boosted the regeneration process compared with pure CUR/CS and the untreated control.